08 IL-17A REGULATES INTESTINAL EPITHELIAL CELLS REGENERATION VIA ATONAL HOMOLOG (ATOH)1. (7th February 2019) - Kumar, Pawan
Abstract: Introduction: IL-17A, derived from Th17 cells, plays an important role in intestinal host defense. However, the interaction and potential molecular synergies between IL-17A and epithelial cell lineages, intestinal stem cells (ISCs), and progenitors of the intestine remain unclear. Materials and Methods: Entire gut epithelium ( Il17ra fl/fl ;Villin-cre )and secretory progenitor and epithelium (Il17ra fl/fl ;Atoh1-cre )-specific IL-17RA knockoutmice were generated. Dextran Sulfate Sodium (DSS) and g-irradiation-mediated epithelial injury and regeneration models were used. Cohoused littermate mice were used in all experiments. RT-PCR, immunofluorescence, and primary enteroid culture were used to study impact of IL-17A signaling on specific cell types. Results: We found that IL-17A/F receptor (IL-17RA/IL-17RC) is expressed on functionally distinct absorptive cells (enterocytes), secretory cells (Paneth), Lgr5+ intestinal stem cells (ISCs) and transit amplifying (TA) progenitor cells of the intestine. Our data show that knockout of IL-17RA from the entire intestinal epithelia in Il17ra fl/fl ;Villin-cre+ miceare more susceptible to DSS- and g-irradiation-mediated epithelial injury. We found a defect in secretory goblet number in DSS-administered Il17ra fl/fl ;villin-cre mice. Atonal homolog 1 (Atoh1) is a transcription factor required for intestinal secretory cell differentiation including goblet and Paneth cells. We found that recombinant IL-17A induced Atoh1 expression in ISCs. Our preliminary data show a more severe DSS and g-irradiation-mediated intestinal injury in Il17ra fl/fl ;Atoh1-cre+ mice. Next, we found reduced Sox9 expression as well as reduced Ki67 + stained cells in the colon of DSS administered Il17ra fl/fl ;Atoh1-cre + mice. Furthermore, we show that IL-17A does not regulate mature goblet cell-specific functions which indicates a stem/progenitor cell-specific defect. Our data suggest that IL-17A via Atoh1 regulates intestinal mucosal host defense. Conclusion: Our data show a novel role of IL-17A in regulating Atoh1-dependent epithelial cell regeneration.